2010
DOI: 10.1086/651951
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology Reveals Long‐Term Changes in HIV Type 1 Subtype B Transmission in Switzerland

Abstract: Our analysis suggests (1) the absence of a self-sustaining epidemic of HIV-1 subtype B in HETs in Switzerland and (2) a temporally decreasing clustering of HIV infections in HETs and IDUs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
198
4
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(227 citation statements)
references
References 32 publications
20
198
4
2
Order By: Relevance
“…The importance of shared language has also been demonstrated by work on the Swiss HIV Cohort Study, which found evidence of preferential within-group transmission among German and French speaking persons. 16 Although we cannot exclude the possibility that the linked non-U.S. sequences from the LANL database were obtained from the same individuals in the U.S. National HIV Surveillance System, these linkages point to international travel of HIV to countries of birth and shared language.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of shared language has also been demonstrated by work on the Swiss HIV Cohort Study, which found evidence of preferential within-group transmission among German and French speaking persons. 16 Although we cannot exclude the possibility that the linked non-U.S. sequences from the LANL database were obtained from the same individuals in the U.S. National HIV Surveillance System, these linkages point to international travel of HIV to countries of birth and shared language.…”
Section: Discussionmentioning
confidence: 99%
“…Transmission networks inferred from genetic sequences allow the study of viral dynamics on a local or national level. [14][15][16][17][18][19] Moreover, these networks provide the means to improve the effect of targeted treatment intervention. 20 Recent work by Wertheim et al 2 has demonstrated how the global diversity of HIV can be efficiently queried for transmission links by comparing genetic distances between isolates.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] However, there is confusion surrounding HIV clustering due to differences in sampling, methodological approaches, and interpretation of HIV clustering results across studies. Issues that still need to be resolved through dedicated studies, meta-analyses, and comprehensive reviews include the following: What is the definition of an HIV cluster?…”
Section: Introductionmentioning
confidence: 99%
“…Achievement of this goal could be facilitated by a better understanding of the structure and dynamics of HIV transmission networks and comprehensive HIV cluster analysis. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] The extent of viral clustering is one of the key factors in making inferences about epidemiologic processes inferred from viral phylogenies. However, it remains to be established how the selection of region across the HIV-1 genome and its length affects the extent of HIV clustering.…”
Section: Introductionmentioning
confidence: 99%